Dissipation of flubendiamide (480 SC) in cardamom [Elettaria cardamomum (L.) Maton] - N Pratheeshkumar, G Xavier, T George, S N Beevi, T B Mathew, (Journal of Spices and Aromatic Crops, 2015)
Insecticide flubendiamide was sprayed thrice at 21 days interval between December-February on cardamom at two concentrations, i.e. 0.72 g a.i. 10 L-1 (X), and 1.44 g a.i. 10 L-1 (2X). Samples of capsules were collected at regular intervals for 15 days after application of the insecticide for residue analysis. The initial deposit of flubendiamide in capsules was 0.42 and 0.60 mg kg-1 for X and 2X treatments, respectively that dissipated with a half-life of 1.25 and 2.53 days, respectively. No residue of des-iodo flubendiamide (the metabolite of flubendiamide) was detected in any of the samples up to 15 days. The limit of quantification (LOQ) of the method was 0.05 mg kg-1, for both flubendiamide and des-iodo flubendiamide.